2000
DOI: 10.1074/jbc.m005387200
|View full text |Cite
|
Sign up to set email alerts
|

Nramp 2 (DCT1/DMT1) Expressed at the Plasma Membrane Transports Iron and Other Divalent Cations into a Calcein-accessible Cytoplasmic Pool

Abstract: Nramp2, also known as DMT1 and DCT1, is a 12-transmembrane (TM) domain protein responsible for dietary iron uptake in the duodenum and iron acquisition from transferrin in peripheral tissues. Nramp2/DMT1 produces by alternative splicing two isoforms differing at their C terminus (isoforms I and II). The subcellular localization, mechanism of action, and destination of divalent cations transported by the two Nramp2 isoforms are not completely understood. Stable CHO transfectants expressing Nramp2 isoform II mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
149
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(156 citation statements)
references
References 43 publications
7
149
0
Order By: Relevance
“…S2C), but not Ca 2+ (Fig. S2D), consistent with previous studies with mammalian Nramp2 homologs (9,11,14,21). However, in contrast to DraNramp M230A, M265A did not transport any of the tested metals, similarly to the D86A loss-offunction phenotype, even though both variants expressed as well as WT (Fig.…”
Section: Significancesupporting
confidence: 79%
See 1 more Smart Citation
“…S2C), but not Ca 2+ (Fig. S2D), consistent with previous studies with mammalian Nramp2 homologs (9,11,14,21). However, in contrast to DraNramp M230A, M265A did not transport any of the tested metals, similarly to the D86A loss-offunction phenotype, even though both variants expressed as well as WT (Fig.…”
Section: Significancesupporting
confidence: 79%
“…Nramps are generally thought to function as metal-proton symporters (1) and are able to bind and/or transport a wide range of divalent transition metal substrates, including the biologically useful metals Mn 2+ , Fe 2+ , Co 2+ , Ni 2+ , Cu 2+ , and Zn 2+ , as well as the toxic heavy metals Cd 2+ , Pb 2+ , and Hg 2+ (4,(9)(10)(11)(12)(13). Nramps do discriminate against the divalent alkaline earth metal ions Mg 2+ and Ca 2+ (9,14), which are typically several orders of magnitude more abundant than the transition metals (15).…”
mentioning
confidence: 99%
“…Based on homology with members of the LeuT superfamily, Nramp1 and DMT1 most likely have pseudo-symmetry with domains 1-6 and domains 7-12 representing N-and C-terminal halves, respectively (44). The loop between domains 7 and 8 is extracellular and glycosylated (57,62). In a curiosity of nature, DMT1 allelic variants have been found in mice (41) and rats (58) with the same G185R substitution in the predicted fourth transmembrane-spanning domain.…”
Section: D169mentioning
confidence: 99%
“…Studies in cultured mammalian cells have also shown that both isoforms of DMT1 are capable of transporting a variety of divalent metal ions across the plasma membrane [12,13]. Transport of these metal ions was shown to occur at pH 5.5, but not at 7.4 [1].…”
mentioning
confidence: 99%